Metode Sorogan Dalam Mengembangkan Kemahiran Membaca Kitab Kuning Santri di Pondok Pesantren Fajrussa’adah - Hadi, Choirul; Nuha, Ulin; Mumin, Rizal Ali; Musaropah, Umi (Universitas Cokroaminoto Yogyakarta, 2024)
This qualitative research, conducted through observation, interviews, and documentation, aims to examine and explore how the sorogan method is implemented, what influences its implementation, and what impacts occur after implementing it. The results show that the Fajrussa’adah Islamic boarding school is one of the Salaf Islamic boarding schools that uses the yellow book and the sorogan method as a source and method in its learning. The implementation takes place three days a week and is held in the evening after the Isha prayer. Several supporting factors include strong student motivation and the presence of a teacher. Several inhibiting factors include students' fatigue after attending formal school outside the boarding school and many feeling sleepy because classes are held at night. Nevertheless, the implementation of sorogan has a significant impact on students in terms of reading and understanding the yellow book and has an impact on their daily lives, making them more mature in preparing things.